TOXICITY OF NITRITE TO THE LARVAE OF PENAEUS INDICUS - Jayasankar, P; Muthu, M S (Indian Journal of Fisheries, 2011)
Short-term experiments revealed that there is a progressive increase in thetolerance of the hirval stages of Penaeus indicus to nitrite. For nauplius, protozoeaand mysis the 24h LC50 values were, respectively, 10.23 mg/1, 20.43 mg/1 and33.87 mg/I NO'2-N, 4S-hLC5o for protozoea was found to be 15.37 mg/1 NO2-N.while long-term experiments showed that the 9-day incipient LC50 was 3.29 mg/1NOj-N. The ECjo. the concentration at which 50% of the larvae did not metamorphoseinto postlarvae in 9 days, for nitrite was 1.8 ppm N02-N. "Safe level"of nitrite that should be maintained in the seawater used for larval rearing wascalculated on the basis of the incipient LC50 value as 0.33 ppm NO2N. Moresensitive estimate of "safe level" based on EC50 value was 0.18 ppm NO'j-N.